Stool Examination Profiles in Malnourished Children - Nisrina Nur Haniyah; Farid Agung Rahmadi; Amallia Nugettsiana Setyawati; Rina Pratiwi (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Stool examination is a gold standard that can be used to detect problems in the disgestive systems, which becomes a preliminary examination to determine a diagnosis. The variation characteristics of stool in malnuorished children are very possible due to the infection in the digestive tract, resulting in impaired absorption of nutrients and other health problems.Objective: To find out the profile of routine feces examination in malnourished children.Methods: This study was descriptive research with a cross-sectional method. This study was conducted from April—August 2021 with a sample size of 38 stunted and malnourished children of 6 month-old to 5-year-old in Rumah Gizi and Poli Anak RSUP Dr. Kariadi Semarang. Collecting the data of anthropometric, quisioners, and laboratorium stool macroscopic and microscopic analytic.Results: Macroscopic examination showed that 13 samples (34.25) had a normal brown color, 35 samples (92.1%) had a soft consistency. Moreover, mucus was found in 6 samples (15.8%). In microscopic examination found that 4 cases (10.5%) were positive for carbohydrates. In 17 cases (44.75), fibers were found. Leukocytes were found in 2 cases (5.2%), erythrocytes were found in 8 cases (21.1%), occult blood was found in 10 cases (26.3%), and fungal positive was found in 14 cases (36.8%).Conclusion: Most of the feces were brown, had soft consistency, did not have mucus and blood. Furthermore, fat, fiber, carbohydrates, leukocytes, erythrocytes, occult bold, and fungal were not found in most of the stools.